Evaluación técnico financiera del uso de un sistema de medición de flujo multifásico en la adquisición de datos de caudales en tiempo real para la prueba de pozos en el campo Platanillo (2019)
In the present work, the description of the generalities from the Platanillo Field will be done, as well as the conventional equipment currently used for well testing, and the multiphase flow meter to be implemented. Subsequently, the implementation of the multiphase meter in the field will be carried out to compare its operation with the equipment that is being currently used. With the data obtained from the multiphase flow meter, a macro will be prepared in Excel. Finally, the viability of the presented project will be analyzed using Net Present Value.